UJI TINGKAT KEKONTRASAN PREPARAT JARINGAN OTOT MENGGUNAKAN PEWARNA ALAMI DARI LARUTAN UMBI BIT (Beta vulgaris L) SEBAGAI SUMBER BELAJAR BIOLOGI - Livia Indri Puasari; Handoko Santoso; Rasuane Noor (Prodi Pendidikan Biologi FKIP Universitas Muhammadiyah Metro, 2020)
Cell or tissue dyes that have been used are synthetic dyes where the chemicals are relatively expensive and carcinogenic in nature. Alternativedyes can be used are natural dyes that have a high affinity for the componentsof cells or tissues. The aim of this study was to determine the contrast level ofmuscle tissue preparations stained using solution (Beta vulgaris L) anddetermine the concentration of solution (Beta vulgaris L) which had the besteffect on the level of muscle tissue contrast.This type of research is an experimental study with qualitativedescriptive data processing, the design uses 6 treatment variations of beetrootconcentration concentration (20%, 50%, 60%, 75%, 90%, 100%) and 2treatments as a control (without coloring and eosin coloring) with 3replications. Data obtained by direct observation using a microscope anddocumented with a camera and then conducted a review by biologists. Theparameter observed was the contrast of the color of the muscle tissuepreparation. The results showed that the contrast level of (Columna livia)skeletal muscle tissue preparations stained using solution (Beta vulgaris L) wasbest at a concentration of 60% was very clear criteria and very contrasted withthe average value obtained 2, 74. The results of this study were compiled as asource of learning biology in the form of practical instructions for class XI highschool students in the structure and function of tissue in animals with anaverage percentage worth of 86%.